Veterinary parasitology - Otranto, Domenico; Wall, Richard (Richard L.); Taylor, M. A. (Mike A.). (Hoboken, NJ : Wiley-Blackwell, 2024)
"In this 5th edition, therefore, we have attempted to reduce repetition, clarify, by removing some of the less important parasites, and to divide the material more clearly into two parts. The first is a taxon-based overview of the biology of key parasites of veterinary importance, their life cycles, morphology, diagnosis and identification along with the general principles of treatment and epidemiology. The second, contains specific clinical details of the pathogenesis, epidemiology, control and treatment of individual parasite species, still structured by host and organ-system. The result, we hope, is an edition that is easier to navigate for readers"--
Veterinary Helminthology -- Veterinary Protozoology -- Veterinary Entomology -- Laboratory diagnosis and identification -- Antiparasitics and resistance -- Innate and acquired resistance, vaccines and alternative approaches to parasite management -- Epidemiology of parasitic disease and the environmental impacts of its management -- Parasites of Cattle -- Parasites of Sheep and Goats -- Parasites of Horses -- Parasites of Pigs -- Parasites of Cats and Dogs -- Parasites of Poultry -- Parasites of Ungulates -- Parasites of Laboratory Animals -- Parasites of Exotics.
Preceded by Veterinary parasitology / M.A. Taylor, R.L. Coop, R.L. Wall. 2016.
Includes bibliographical references and index.
Keywords: Animals, Domestic -- parasitology; Parasitic Diseases, Animal